Serum PCSK9 is modified by interleukin-6 receptor antagonism in patients with hypercholesterolaemia following non-ST-elevation myocardial infarction - Ueland, Thor (Open Heart, 2018)
OBJECTIVE: It is unclear if activation of inflammatory pathways regulates proprotein convertase subtilisin-kexin type 9 (PCSK9) levels. APPROACH: We evaluated (1) the temporal course of serum PCSK9 during hospitalisation following acute coronary syndrome and associations with markers of inflammation (leucocyte counts, interleukin (IL)-6, C-reactive protein) and lipid levels and (2) the effect of inhibition of IL-6 signalling with the IL-6 receptor antibody tocilizumab on PCSK9 levels in a randomised, double-blind, placebo-controlled trial release in patients with non-ST-elevation myocardial infarction. RESULTS: Serum PCSK9 increased during the acute phase and this response was modestly associated with neutrophil counts (r=0.24, p=0.009) and presence of hypercholesterolaemia (r=0.019, p=0.045), but was not modified by tocilizumab. However, a modifying effect of tocilizumab on PCSK9 levels was observed in patients with hypercholesterolaemia (p=0.024, repeated measures analysis of variance) and this effect was strongly correlated with the decrease in neutrophils (r=0.66, p=0.004). CONCLUSIONS: Our study suggests that patients with a more atherogenic profile may benefit from anti-IL-6 therapy with regard to PCSK9. TRIAL REGISTRATION NUMBER: NCT01491074.